RE:SLAB—a load bearing system for open-ended component reuse in building structures - Estrella, Xavier; Muresan, Alex; Brütting, Jan; Redaelli, Dario; Fivet, Corentin (Frontiers in Built Environment, 2024)
The construction industry plays a major role in the high levels of greenhouse gas emissions, resource consumption, and waste generation observed nowadays. Key to the circular economy, structural component reuse arises as a promising solution to divert construction waste from landfilling and avoid the production of new components. In this context, this paper presents the conceptual design of a new slab-and-column system called “Re:Slab”, optimized for disassembly and open-ended reassembly over multiple building lifespans. Beyond conventional considerations of modular sizing and reversible connections, the proposed system provides designers with a minimum kit of parts that is capable of exceptionally diverse building layouts–e.g., related to floor geometry, span between supports, applied loads, and spatial transformations. Attention is given to easily operable assembly and disassembly techniques, embodied environmental impacts, and manufacturing costs. As a result, the proposed system reaches unprecedented high levels of versatility, making it capable of adapting to future functional design requirements that are hard to predict over long-term social developments. Options for increased economic viability are identified, which are necessary to promote widespread adoption of the system.